Cell Line Authentication (CLA) using Short Tandem Repeat (STR) Method on Breast Cancer cell line MCF-7 - Pendrianto; Muhammad Samsul Mustofa; Silviatun Nihayah (Future Science)
Research on human diseases, especially in cancer begins with in vitro studies using cell lines. However, cell lines grown in vitro can occur cross-contamination or even miss-identification. This requires a cell line authentication (CLA) procedure using a molecular approach. In this process, analysis of allele variance from several loci is needed to ensure that this variant matches the expected allele. The STR method can be used to authenticate cell lines, because it can compare allele profiles with a sample of known standard cell lines, and also able to provide simple, inexpensive, and very specific genetic